ANALISIS PENGARUH TINGKAT KEMANDIRIAN FISKAL DAN BELANJA MODAL DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA KABUPATEN / KOTA DI PROVINSI JAWA TIMUR TAHUN 2009 - 2013 - Taufick, Aditya Iman (Jurnal Ilmiah Mahasiswa FEB, 2015)
National development can be realized if the regional development berrjalan well. And regional development will be realized if the region to improve the quality of society (human development). Human development can be measured by the Human Development Index (HDI), where the indicator is on education, health and decent living standards. HDI districts and cities in East Java province tends to increase every year and are in the middle position of the HDI. The level of local fiscal autonomy will affect the welfare of a region depends on how local governments prioritize revenue allocation. With a few variables have been determined, the study aims to: (1) know how to influence fiscal independence of the HDI districts in East Java province, (2) know how to influence capital spending areas of the HDI districts in East Java province, ( 3) determine how the development of fiscal independence 38 counties and cities in East Java province. The place and time of this study are in all districts and cities in East Java during 2009 - 2013. The analytical method to be used is the panel data regression. Results of the study using a fixed effect model showed that fiscal independence and local capital expenditure and significant positive effect on the human development index.Keywords : Human Development Index, Fiscal Autonomy, the Regional Capital Expenditure